Устойчивость гофрированных арок при внешнем давлении - Семенюк, Н.П. (Прикладная механика, 2013)
A technique is proposed for analysis of stability and post-critical behaviour of the goffered arches. It is based on solving the nonlinear system of the first order ordinary differential equations with using the method of incremental loadings. The boundary problem in increments is solved by the method of discrete orthogonalization. The solutions of particular problems of stability for the goffered arches showed that behaviour such structures differs essentially from behaviour of the circular arches.